A role for the vesicle-associated tubulin binding protein ARL6 (BBS3) in flagellum extension in Trypanosoma brucei - Price,HP; Hodgkinson,MR; Wright,MH; Tate,EW; Smith,BA; Carrington,M; Stark,M; Smith,DF (Biochimica et Biophysica Acta-Molecular Cell Research, 2012)
The small GTPase Arl6 is implicated in the ciliopathic human genetic disorder Bardet–Biedl syndrome, actingat primary cilia in recruitment of the octomeric BBSome complex, which is required for specific traffickingevents to and from the cilium in eukaryotes. Here we describe functional characterisation of Arl6 in the flagellatedmodel eukaryote Trypanosoma brucei, which requires motility for viability. Unlike human Arl6 whichhas a ciliary localisation, TbARL6 is associated with electron-dense vesicles throughout the cell body followingco-translational modification by N-myristoylation. Similar to the related protein ARL-3A in T. brucei, modulationof expression of ARL6 by RNA interference does not prevent motility but causes a significant reductionin flagellum length. Tubulin is identified as an ARL6 interacting partner, suggesting that ARL6 may act as ananchor between vesicles and cytoplasmic microtubules. We provide evidence that the interaction betweenARL6 and the BBSome is conserved in unicellular eukaryotes. Overexpression of BBS1 leads to translocationof endogenous ARL6 to the site of exogenous BBS1 at the flagellar pocket. Furthermore, a combination ofBBS1 overexpression and ARL6 RNAi has a synergistic inhibitory effect on cell growth. Our findings indicatethat ARL6 in trypanosomes contributes to flagellum biogenesis, most likely through an interaction with theBBSome